Kinetic properties of alternatively spliced isoforms of laccase-2 from Tribolium castaneum and Anopheles gambiae - Gorman, Maureen J.; Sullivan, Lucinda I.; Nguyen, Thi D.T.; Dai, Huaien; Arakane, Yasuyuki; Dittmer, Neal T.; Syed, Lateef U.; Li, Jun; Hua, Duy H.; Kanost, Michael R. (My University, 2012)
Laccase-2 is a highly conserved multicopper oxidase that functions in insect cuticle pigmentation and tanning. In many species, alternative splicing gives rise to two laccase-2 isoforms. A comparison of laccase-2 sequences from three orders of insects revealed eleven positions at which there are conserved differences between the A and B isoforms. Homology modeling suggested that these eleven residues are not part of the substrate binding pocket. To determine whether the isoforms have different kinetic properties, we compared the activity of laccase-2 isoforms from Tribolium castaneum and Anopheles gambiae. We partially purified the four laccases as recombinant enzymes and analyzed their ability to oxidize a range of laccase substrates. The predicted endogenous substrates tested were dopamine, Nacetyldopamine (NADA), N-b-alanyldopamine (NBAD) and dopa, which were detected in T. castaneum previously and in A. gambiae as part of this study. Two additional diphenols (catechol and hydroquinone)and one non-phenolic substrate (2,20-azino-bis(3-ethylbenzthiazoline-6-sulphonic acid)) were also tested. We observed no major differences in substrate specificity between the A and B isoforms. Dopamine, NADA and NBAD were oxidized with catalytic efficiencies ranging from 51 to 550 min 1 mM 1. These results support the hypothesis that dopamine, NADA and NBAD are endogenous substrates for both isoforms of laccase-2. Catalytic efficiencies associated with dopa oxidation were low, ranging from 8 to 30 min 1 mM 1; in comparison, insect tyrosinase oxidized dopa with a catalytic efficiency of 201 min 1 mM 1. We found that dopa had the highest redox potential of the four endogenous substrates, and this property of dopa may explain its poor oxidation by laccase-2. We conclude that laccase-2 splice isoforms are likely to oxidize the same substrates in vivo, and additional experiments will be required to discover any isoform-specific functions.
Citation: Gorman, M.J., Sullivan, L.I., Nguyen, T.D.T., Dai,H., Arakane,Y., Dittmer, N.T.,…Kanost, M.R. (2012). Kinetic properties of alternatively spliced isoforms of laccase-2 from Tribolium castaneum and Anopheles gambiae. Insect Biochemistry and Molecular Biology, 42(3), 193-202.
Keywords: Multicopper oxidase; Laccase; Substrate; Insect; Cuticle